الطقوس والمعتقدات المصاحبة لزيارة ضريح الحبيب نوح بن محمد الحبشي بسنغافورة في ضوء القرآن والسنة - Sharifah Nadirah Nasibah Binti Ahmad Alja'fari
The Sunnah of Nabawiyyah has come with accurate guidance so that you will unite and not split, so that you will benefit and not get harm. The Prophet's Sunnah bequeth for you to be gentle in giving advices and corrections as well as being civic-minded when teaching. And when Muslims become negligent towards these meanings, they will be weak in maintaining harmonious relationships due to several reasons even the smallest of matters can cause rifts and separation and able to divide their unity. They are unable to understand the conflict and respect for diversity, and therefore the parties who do not agree with them will be accused as heretics, apostates and would not get the intercession of the prophet in the afterlife. Among those who pose a threat to the unity of the Muslims, especially in Singapore is a matter of visiting the grave of Habib Nuh Al-Habshi. Beginning from this issue, this study was written with the purpose of gathering the opinions of scholars and their authority in matters related with visiting him, hoping that we can approach the existing differences. The highlight of this study and its speciality lies on the topic being discussed, because from the author's knowledge, this is the first study conducted on issues related to visiting Habib Nuh to gather proof of the opinions and their understanding of the traditions of the Prophet and the problem to visit grave. Other writers have previously only gather the opinions and arguments of a group without accompanying opinions and proof of the contrary. It is expected to issue within a matter of understanding and respect to the others. The author of the study starts with explaining a bit about Habib Nuh and his background after which the issue on visiting graves while debating manners and moving to see him. After that the author presents the act is commonly done by visitors of Habib Nuh to his tomb either by the Muslims or otherwise. Descriptive approach was adopted in light of what is happening around the tomb of Habib Nuh while inductive approach is used in the methodology of this study to collect the opinions of scholar's arguments. The analytical and critical reasoning are used to discuss the views of scholars and the arguments for them that can stand on the dispute. In addition to getting information through the library, the author also interviewed those responsible for maintaining the grave of Habib Nuh and pilgrims as well as keep an eye of the situation prevailing in the tomb. This study has been successful in getting some results, among which the most important is, that the disputing parties in an awliya have had to visit the rest of the evidence and follow the venerated scholar and the truth will not become falsehood just because public opinion is againts it and falsehood is not going to be the truth just because public opinion is align with it and the Muslims will not be expelled from their religion just because their thoughts are not align with khilafiyah related issues. As a result, this writing was done to treat the large gaps based on Prophet's concern so that Muslims will not be hard towards their own peers.